POST-RIFT VERTICAL MOVEMENTS OF THE SOUTHERN AFRICANMARGINS-IMPLICATIONS FOR THE SOUTH AFRICAN PLATEAUUPLIFT - (:unkn) unknown (My University, 2017)
The South African (Kalahari) Plateau is the world’s largest non-orogenic plateau. It forms a largescaletopographic anomaly (×1000 km) which rises from sea level to > 1000 m. Most mechanisms proposed toexplain its elevation gain imply mantle processes. The age of the uplift and the different steps of relief growthare still debated. On one hand, a Late Cretaceous uplift is supported both by thermochronological studies andsedimentary flux quantifications. On the other hand, geomorphological studies suggest a Late Cenozoic upliftscenario.Onshore, on the mapping and chronology of all the macroforms (weathering surfaces and associatedalterites, pediments and pediplains, incised rivers, wave-cut platforms) dated by intersection with the fewpreserved sediments and the volcanics (mainly kimberlites pipes).Offshore, on a more classical dataset of seismic lines and petroleum wells, coupled with biostratigraphicrevaluations (characterization and dating of vertical movements of the marginssediment volumemeasurement).The main result of this study is that the South African Plateau is an old Upper Cretaceous relief (90-70Ma) reactivated during Oligocene (30-15 Ma) times. Its evolution can be summarized as follows:• 100-70 Ma (Cenomanian to Campanian): low elevation plateau (0-500 m) with older and higher reliefslocated along the Indian side, acting as a main divide between the Atlantic and the Indian Oceans. First upliftoccurred in the east at ~92 Ma, with a fast flexuration of the Indian margins. This initiates a paroxysm of theerosion (90-80 Ma) with the growth of a large delta along the Atlantic margin (Orange delta). Deformationmigrated progressively westward and resulted on the growth of the Atlantic marginal bulge between 81 and70 Ma. Most of the present-day relief was probably created at this time. This is supported by the decrease ofthe sedimentary flux which suggests a reorganisation of the interior drainage pattern.• 70-30 Ma (Uppermost Cretace
Keywords: African Research